Impact of physicochemical properties on band gap energy and glass transition temperature of (GeS2)10(Sb2S3)90−x(AgI)x chalcohalide glasses for Near-IR applications. (25th January 2021) - Boukhris, Imed; Hegazy, H H
Abstract: The dependence of band gap energy (Eg ) and glass-transition temperature (Tg ) on physico-chemical properties for the (GeS2 )10 (Sb2 S3 )90−x (AgI)x (10 ≤ x ≤ 50 at%) chalcohalide glasses were theoretically investigated. Chalcohalide glasses have wide technological applications owing to the aptitude of tuning their optical band gap through composition change. Therefore, Eg of the studied chalcohalide glasses was estimated using different methods, and it was turned out that it decreased as the AgI amount increases. This decrease was elucidated in terms of physico-chemical properties. In addition, we determined the positions of conduction band (ECB ) and valence band (EVB ) by using the computed values of Eg . The density and molar volume increased while the packing density decreased by adding AgI. The overall coordination number (CN), crosslinking density (CD), constraints number (Ns ), cohesive energy (CE), heat of atomization (Hs ) and overall mean bonds energy (⟨E⟩); computed via the chemical bond approach (CBA); decreased with the increment of AgI amount. In contrary, the floppy (F) and mean bonds energy (Es ) increased. Finally, two estimations of Tg were presented based on ⟨E⟩ and CN. The two estimations showed a decreasing trend when adding AgI content.